The Influence of Electronic Word of Mouth (eWOM) and Product Quality on Buyer Decisions of MSME Angkringan Moderated Trust - Lukiyana Lukiyana; Rachel Rosiva (Budapest International Research and Critics University, 2022)
This study aims to determine trust as a moderating variable on the influence of Electronic Word of Mouth (eWOM) and Product Quality on Buyer Decisions. This study uses quantitative methods, with data collection techniques by distributing questionnaires through google form. The results of this study indicate that E-WOM, Product Quality, and trust have a positive and significant effect on buyer decisions, moderating trust on the influence of E-WOM has no effect on buyer decisions and moderating trust on the effect of product quality has no effect on buyer decisions.